Vitamin D Receptor Fok-I Polymorphism Modulates Diabetic Host Response to Vitamin D Intake: Need for a nutrigenetic approach - Neyestani, Tirang R. (American Diabetes Association, 2013)
OBJECTIVE: Interpopulation as well as interindividual variations in response to vitamin D intake commonly observed in subjects with type 2 diabetes may be related to genetic makeup. One of the candidate genes potentially responsible for this diversity is vitamin D receptor (VDR). This study aimed to investigate the interactive effect of VDR Fok-I polymorphism and vitamin D intake on diverse aspects of diabetic host response. RESEARCH DESIGN AND METHODS: Glycemic status, lipid profiles, inflammatory biomarkers, and VDR Fok-I genotypes were determined in diabetic subjects (n = 140) who participated in a randomized controlled trial. Participants consumed two 250-mL bottles per day of yogurt drink (doogh) fortified with 500 IU vitamin D/250 mL for 12 weeks. RESULTS: Mean serum 25(OH)D increased by ~30 nmol/L (P < 0.001). The time × intervention effect was significant for 25(OH)D (P = 0.030), HDL (P = 0.011), high-sensitivity C-reactive protein (hsCRP) (P < 0.001), interleukin (IL)-4 (P = 0.008), and IL-6 (P = 0.017) among the genotypic groups. The alleles were defined as ‘‘F’’ or ‘‘f’’ depending on the absence or presence of the restriction site, respectively. The least increment in 25(OH)D was in ff (23.0 ± 3.8 nmol/L) compared with Ff (31.2 ± 3.4 nmol/L) and FF (35.6 ± 2.7 nmol/L) (P for trend = 0.009), but only the difference between ff and FF was significant (P = 0.023). FF group had the largest decrement of both hsCRP and IL-6 compared with Ff (P < 0.001 and P = 0.038) and ff (P = 0.010 and P = 0.048), respectively. CONCLUSIONS: We concluded that those of VDR ff genotype may be regarded as “low responders” to vitamin D intake in terms of response of circulating 25(OH)D and certain inflammatory biomarkers. A nutrigenetic approach may, therefore, be needed to protect diabetic patients from vitamin D deficiency.